Mind-Mapping Migration: Understanding the Deeper Contours of a Contentious Debate - Groody, Daniel G. (Transformation, 2018)
This article discusses the issue of migration from various vantage points: political, economic, linguistic, legal, philosophical, and ethical. It is shown that although migration touches upon many areas of human life, it is in reality a straightforward issue. It is basically about human beings in search for a more dignified life. The author critiques the operative dualisms that characterize the migration debate, in doing so undermining the dehumanizing thinking that gives birth to such rhetoric, and suggests an approach to the issue that fosters a transformation rooted in authentic human and spiritual development.